Can green finance policy reduce energy consumption: quasi-natural experimental evidence from green finance reform and innovations pilot zone - Lv, Lu; Guo, Bingnan (Frontiers in Environmental Science, 2025)
IntroductionThe Green Finance Pilot Policy is a crucial initiative in China’s green finance reform, playing a significant role in reducing energy consumption and achieving carbon neutrality goals. This study examines whether the establishment of green finance reform and innovation pilot zones effectively reduces energy consumption and explores the underlying mechanisms of its impact.MethodsUsing panel data from 30 provincial-level administrative regions in China from 2013 to 2021, this study employs the staggered Difference-in-Differences (DID) model as a quasi-natural experiment. The analysis evaluates the effect of green finance reform policy on energy consumption and investigates the mediating effects of industrial structure optimization and green innovation.ResultsThe results indicate that the green finance reform and innovation pilot zones significantly reduce energy consumption levels, and this conclusion remains robust after a series of robustness tests. Mechanism analysis reveals that the policy primarily reduces energy consumption by optimizing industrial structure and promoting green innovation.DiscussionThese findings provide new evidence for understanding the impact of green finance reform pilot zones on energy consumption and offer insights for further unlocking the energy-saving potential of green finance policy. The study suggests deepening institutional frameworks, establishing long-term support mechanisms, and optimizing policy implementation strategies to enhance the effectiveness of green finance policy in energy conservation and emissions reduction.